O gênero notícia no ensino médio : do modelo autônomo ao ideológico de letramento - Silva, Ana Maria da (2012)
This action research qualitative aims to understand the process of literacy or the journalistic genre literacy news on high school students. Therefore, supported mainly on the assumptions and theoretical studies of Bakhtin (2010), Bronckart (2003), Kleiman (2009) and in research on literacy in perspective´s sociointeracionist, we intend to address the promotion of media literacy in high school, from structural study, language, and genre themed news, reflecting on the development of language skills. At this point, the theory of language Sociodiscursiva Interactionist theory, this research supports the measure it considers a subject (a student of third year high school), an object on which it acts (genre News) mediators and tools useful to the extent of appropriation desired (activities / teaching tools) (Schneuwly, 2000). To achieve the overall goal, specific objectives are: to assess the language skills developed in the initial production and final look at the role of the tools / instruments for the appropriation of the genre news, observe the development of literacy related to the journalistic sphere. Although literacy is not restricted to the school environment in Brazil, officially the period devoted to basic education is generally understood as the time to learn what it takes to become a citizen capable of dealing with the challenges of social life outside the school. This means that for those who are in touch daily with the multiple languages, it is essential to understand, interpret, and, above all, evaluate the content transmitted. From this perspective, be literate transcends the idea of understanding, configuring itself as discerning about what they read, hear and see. The approach of journalistic texts in school is particularly relevant, since its receipt, which occurred early in the home, is rarely accompanied by reflections on their production conditions and objectives of the author to the reader forward. So is the school responsibility to guide and promote access to knowledge of these cultural objects. In the 3rd year high school, the concern with passing the entrance examination to teaching print contents clearly a bias to the detriment of character formation. For this reason, I took students as research subjects in this series, from a private school in the northwest region of Paraná.